2017
DOI: 10.1007/978-3-319-70139-4_78
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Stroke Using Deep Learning Model

Abstract: Many predictive techniques have been widely applied in clinical decision making such as predicting occurrence of a disease or diagnosis, evaluating prognosis or outcome of diseases and assisting clinicians to recommend treatment of diseases. However, the conventional predictive models or techniques are still not effective enough in capturing the underlying knowledge because it is incapable of simulating the complexity on feature representation of the medical problem domains. This research reports predictive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 15 publications
0
7
0
2
Order By: Relevance
“…Prediksi stroke pada pasien bertujuan untuk mengurangi potensi kematian yang disebabkan stroke. Model prediksi dengan, pembelajaran mesin telah diusulkan, antara lain menggunakan Chi-Square (Chi-2), Decision Tree [3], Two-Class Boosted Decision Tree [4], Naive Bayes, Support Vector Machine [5], Logistic Regression, Random Forest, Gradient Boosting [6]. Metoda yang diusulkan pada referensi tersebut diuji dengan menggunakan dataset yang berbeda-beda dan menghasilkan nilai akurasi yang bervariasi.…”
Section: Pendahuluanunclassified
“…Prediksi stroke pada pasien bertujuan untuk mengurangi potensi kematian yang disebabkan stroke. Model prediksi dengan, pembelajaran mesin telah diusulkan, antara lain menggunakan Chi-Square (Chi-2), Decision Tree [3], Two-Class Boosted Decision Tree [4], Naive Bayes, Support Vector Machine [5], Logistic Regression, Random Forest, Gradient Boosting [6]. Metoda yang diusulkan pada referensi tersebut diuji dengan menggunakan dataset yang berbeda-beda dan menghasilkan nilai akurasi yang bervariasi.…”
Section: Pendahuluanunclassified
“…The study reported the significance of the phenotypic form of classifying stroke and it explains the absence of trustworthiness in results. [16] introduced a stroke prediction model by the use of deep learning. The facts related to the issues in healthcare sector cannot be identified properly using the conventional prediction techniques.…”
Section: Related Workmentioning
confidence: 99%
“…The model achieved accuracy, sensitivity and specificity of 86.5%, 82.9% and 89.7%, respectively. Goyal et al [15] used a heart disease dataset for the predictive analysis of stroke by deep learning technology. Sun et al presented a method for treating functional electrical stimulation (FES) by using a finite state machine (FSM) which has been shown to be effective using additive data by accelerometer according to the calculated gain.…”
Section: Introductionmentioning
confidence: 99%